2009
DOI: 10.1590/s0100-204x2009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Características anatômicas de mudas de morangueiro micropropagadas com diferentes fontes de silício

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de diferentes fontes de silício, utilizadas na micropropagação, nas características anatômicas de mudas de morangueiro (Fragaria x ananassa). Foram utilizados propágulos da cv. Oso Grande cultivados em meio Murashige e Skoog (MS), acrescido de 30 g L -1de sacarose, 6 g L -1 de ágar e 1 mg L -1 de 6-benzilaminopurina. Os tratamentos consistiram da adição ao meio MS dos silicatos de cálcio, de sódio e de potássio, na dosagem de 1 g L -1 . O tratamento testem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 9 publications
(9 reference statements)
2
17
0
11
Order By: Relevance
“…2). This finding concurs with that reported by Braga et al (2009) who observed an increase in the number of leaves in strawberry trees (Fragaria × ananassa) with sodium silicate supplementation of MS medium. There were no significant differences in the number of leaves across potassium silicate concentrations (Fig.…”
Section: Number Of Leavessupporting
confidence: 93%
“…2). This finding concurs with that reported by Braga et al (2009) who observed an increase in the number of leaves in strawberry trees (Fragaria × ananassa) with sodium silicate supplementation of MS medium. There were no significant differences in the number of leaves across potassium silicate concentrations (Fig.…”
Section: Number Of Leavessupporting
confidence: 93%
“…In the presence of up to 10 mg·L −1 sodium silicate, a decrease in shoot mass was observed. Braga et al (2009) observed no statistical differences for fresh and dry shoot masses in 'Oso Grande' strawberry seedlings grown in MS medium with and without addition of sodium and potassium silicate. No statistical differences were observed between treatments for the water content of the shoots.…”
Section: Resultsmentioning
confidence: 65%
“…However, as the concentration of Si increased, a small decline in water content was observed; the water content was 91% in the treatment without addition of Si, and 89% in the treatment containing a concentration of 2 g·L −1 Si. Braga et al (2009) observed that the presence of sodium and calcium silicate in MS medium significantly reduced the water content of 'Oso Grande' strawberry shoots compared to the control medium, MS medium without added silicates. These treatments are thus associated with higher accumulation of dry matter compared to fresh weight.…”
Section: Resultsmentioning
confidence: 86%
“…Lim et al (2012) also reported that the effect of Si (K 2 SiO 3 ) on the growth traits of begonia ‘Super Olympia Red’ and ‘Super Olympia Rose’ and pansy ‘Matrix White Blotch’ and ‘Matrix Yellow Blotch’ are mainly dependent on the cultivars. Braga et al (2009) investigated the effect of different Si sources such as CaSiO 3 , K 2 SiO 3 , and Na 2 SiO 3 on the growth and anatomical characteristics of strawberry ‘Oso Grande’ seedlings. The fresh and dry weight of seedlings increased in MS medium containing 1.0 g L -1 Na 2 SiO 3 .…”
Section: Growth and Developmentmentioning
confidence: 99%